Desenvolvimento de um Chatbot para apoio a elaboração de redação de patentes - ARAUJO, Cyntia Marques (2023)
Intellectual property guarantees legal protection to human creations, granting the temporary right of commercial exploitation. The objective of this work is to develop a ChatBot to systematize the stages of the elaboration of a Patent Writing with an approach in the engineering area, and based on normative instructions 030 and 031/2013. In this way, the ChatBot asks a set of questions, following the order of structure of a Patent essay, and in each question it will have guidance for the user to answer and understand as a friendly conversation. Through the answers provided, generate the written document, filled with the information given by the user about his invention. This document will be the Descriptive Report and the focus area of the Chatbot is Civil Engineering. The work was characterized as technological and applied research in terms of its purpose; descriptive and exploratory research, in relation to the proposed objectives; and bibliographic and survey research regarding technical procedures. A prospective study was carried out for prior art searches of software aimed at chatbots to support the elaboration of patents, but no similar national software was identified. The chatbot brand was elaborated, which was preceded by a prior art search on the INPI website. And also, the submission of the article in a scientific journal.